2013
DOI: 10.1177/0963662512473212
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics in the news: Health and hygiene in the press in periods of crisis

Abstract: How did scientific knowledge reach the public? Using the press and keeping in mind the population's limited access to written material, this paper establishes how the latest scientific news was divulged to unspecialised audiences. In times of sanitary crisis in Oporto, such as the cholera morbus epidemic of 1854-1856, the bubonic plague in 1899 and the 1918 influenza pandemic, newspapers were important sources to access the information and advice given to the public. A database of 6700 articles, medical report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…It marked the end of World War 1 and the beginning of an outbreak of an influenza pandemic that killed more people than the war. Recent studies have revealed an estimate fluctuating from 50 to 100 million casualties worldwide (De Almeida, 2013). It came in phases and encircled the world through increased human mobility, especially via sea route transportation.…”
Section: Influenza: Spread Morbidity and Clinical Manifestationsmentioning
confidence: 99%
“…It marked the end of World War 1 and the beginning of an outbreak of an influenza pandemic that killed more people than the war. Recent studies have revealed an estimate fluctuating from 50 to 100 million casualties worldwide (De Almeida, 2013). It came in phases and encircled the world through increased human mobility, especially via sea route transportation.…”
Section: Influenza: Spread Morbidity and Clinical Manifestationsmentioning
confidence: 99%
“…Overall, ideology determines what is considered STEM news by journalists and producers/editors and the interpretation of the information is strongly entangled with ideological viewpoints (Carvalho, 2007). This results in a narrowing of STEM science topics discussed in the news media, with a general focus on issues that affect the daily lives of individuals (Hansen, 1994) such as biomedicine (Bucchi & Mazzolini, 2003), health issues (Almeida, 2013;Pettersen, 2005;Hansen, 1994), behavioural studies (Clark & Illman, 2006), and environmental stories (Einsiedel, 1992).…”
Section: Who/what Influences Which Stories Are Chosenmentioning
confidence: 99%
“…The significance of the 1918-19-influenza pandemic could not be over-emphasised in modern history because of the overwhelming fatalities attributed to the contagion. The epidemic killed roughly between 50 and 100 million people globally (De Almeida, 2013). Colonial India remained one of the worst-hit nations, with an estimated mortality of 13 million (Chandra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%